Low-amplitude, left vagus nerve stimulation significantly attenuates ventricular dysfunction and infarct size through prevention of mitochondrial dysfunction during acute ischemia-reperfusion injury - Krekwit Shinlapawittayatorn (2018)
Background Right cervical vagus nerve stimulation (VNS) provides cardioprotective effects against acute ischemia-reperfusion injury in small animals. However, inconsistent findings have been reported. Objective To determine whether low-amplitude, left cervical VNS applied either intermittently or continuously imparts cardioprotection against acute ischemia-reperfusion injury. Methods Thirty-two isoflurane-anesthetized swine (25-30 kg) were randomized into 4 groups: control (sham operated, no VNS), continuous-VNS (C-VNS; 3.5 mA, 20 Hz), intermittent-VNS (I-VNS; continuously recurring cycles of 21-second ON, 30-second OFF), and I-VNS + atropine (1 mg/kg). Left cervical VNS was applied immediately after left anterior descending artery occlusion (60 minutes) and continued until the end of reperfusion (120 minutes). The ischemic and nonischemic myocardium was harvested for cardiac mitochondrial function assessment. Results VNS significantly reduced infarct size, improved ventricular function, decreased ventricular fibrillation episodes, and attenuated cardiac mitochondrial reactive oxygen species production, depolarization, and swelling, compared with the control group. However, I-VNS produced the most profound cardioprotective effects, particularly infarct size reduction and decreased ventricular fibrillation episodes, compared to both I-VNS + atropine and C-VNS. These beneficial effects of VNS were abolished by atropine. Conclusions During ischemia-reperfusion injury, both C-VNS and I-VNS provide significant cardioprotective effects compared with I-VNS + atropine. These beneficial effects were abolished by muscarinic blockade, suggesting the importance of muscarinic receptor modulation during VNS. The protective effects of VNS could be due to its protection of mitochondrial function during ischemia-reperfusion. © 2013 Heart Rhythm Society.